Active for Life Year 5: a cluster randomised controlled trial of a primary school-based intervention to increase levels of physical activity, decrease sedentary behaviour and improve diet - Debbie A Lawlor; Ruth R Kipping; Emma L Anderson; Laura D Howe; Catherine R Chittleborough; Aida Moure-Fernandez; Sian M Noble; Emma Rawlins; Sian L Wells; Tim J Peters; Russell Jago; Rona Campell (NIHR Journals Library, 2016)
Background: Previous studies of the effect of school-based interventions to improve healthy behaviours have had important limitations. Objective: To investigate the effectiveness of a school-based intervention to increase physical activity, reduce sedentary behaviour and increase fruit and vegetable consumption. Design: Cluster randomised controlled trial. Setting: Sixty English primary schools. Participants: Children in year 4 (aged 8-9 years) at recruitment, year 5 (aged 9-10 years) during the intervention and immediate follow-up and year 6 (aged 10-11 years) during 1 year of follow-up. Intervention: Active for Life Year 5 (AFLY5) included teacher training, lesson plans, materials for 16 lessons, parent-interactive homework and written materials for school newsletters and parents. Main outcome measures: Primary outcome measures included accelerometer-assessed levels of physical activity and sedentary behaviour, and child-reported consumption of fruit and vegetables. Secondary outcome measures included child-reported screen viewing; consumption of snacks, high-fat food and high-energy drinks; body mass index; and waist circumference. Results: We recruited 60 schools (2221 children). At the immediate follow-up, no difference was found between children in intervention and control schools for any of the three primary outcomes. The intervention was effective on three of the nine secondary outcomes; children in intervention schools reported spending less time screen viewing at weekends [-21 minutes per day, 95% confidence interval (CI) -37 to -4 minutes per day], eating fewer servings of snacks per day (-0.22, 95% CI -0.38 to -0.05 servings of snacks per day) and drinking fewer servings of high-energy drinks per day (-0.26, 95% CI -0.43 to -0.10 servings of high-energy drinks per day) than the children in control schools. The results remained consistent 1 year later. The intervention increased children's perception of maternal efforts to limit the time they spent screen viewing and children's knowledge about healthy physical activity and fruit and vegetable consumption, with these two mediators explaining approximately one-quarter of the effect of the intervention on screen viewing. The intervention did not affect other mediators. The cost of implementing the intervention from a provider perspective was approximately £18 per child. Process evaluation showed that AFLY5 was implemented with a high degree of fidelity. Teachers supported the aims of AFLY5, but their views of the programme itself were mixed. Limitations: Responses to parental questionnaires for the economic evaluation were low and we struggled to engage all teachers for the process evaluation. Although the participating schools included a range of levels of socioeconomic deprivation, class sizes and rural and urban settings, we cannot assume that results generalise to all primary schools. Conclusions: AFLY5 is not effective at increasing levels of physical activity, reducing sedentary behaviour and increasing fruit and vegetable consumption in primary school children, but may be effective in reducing time spent screen viewing at weekends and the consumption of snacks and high-energy drinks. Future work: Our findings suggest that school-based interventions are unlikely to have a major impact on promoting healthy levels of physical activity and healthy diets in primary school children. We would recommend trials of the effect and cost-effectiveness of more intensive family and community interventions. Trial registration: Current Controlled Trials ISRCTN50133740. Funding: This project was funded by the National Institute for Health Research Public Health Research programme and will be published in full in Public Health Research; Vol. 4, No. 7. See the NIHR Journals Library website for further project information.